MAKING QUEER KNOWLEDGE VISIBLE: DEBBY SAHERTIAN AND THE DIGITAL ARCHIVING OF INDONESIAN QUEER TECHNOLECT ON TIKTOK - Januarsyah, Gilang; Finalia, Cicu (Universitas Padjadjaran, 2026)
This study explores how Indonesian queer linguistic knowledge becomes visible and preserved through digital platforms by focusing on a single TikTok video uploaded by Debby Sahertian on 7 July 2021. Known for documenting queer slang (bahasa gay/bahasa gaul) in the late 1990s, Sahertian’s presence on TikTok represents a shift from earlier print-based documentation toward platform-mediated, audiovisual forms of linguistic knowledge production. Drawing on queer sociolinguistics, digital archiving studies, and platform theory, this research conceptualizes TikTok as an informal, community driven archive where marginalized linguistic practices can be demonstrated, interpreted, and transmitted across generations. Methodologically, the study employs qualitative content analysis of the selected video, examining queer technolectal utterances, their lexical and phonetic features, and the metalinguistic explanations provided by Sahertian. These explanations function not merely as translations but as pedagogical and archival strategies that make in-group language intelligible while maintaining its social markedness. The video’s sustained engagement, evidenced by millions of views and ongoing viewer interaction several years after its publication, suggests that it continues to operate as an active and accessible digital artifact. The findings show that Sahertian’s digital practices perform multiple intersecting functions: documenting queer linguistic creativity, facilitating intergenerational knowledge transmission, and countering the historical exclusion of queer voices from formal linguistic and cultural archives. At the same time, TikTok’s algorithmic visibility remains ambivalent, simultaneously expanding access to queer linguistic knowledge while exposing it to surveillance and commodification. Overall, this study argues that digital platforms play an important role in shaping how Indonesia’s queer linguistic past is remembered, negotiated, and carried forward.